Influência do meio de cultura na contagem de bactérias psicrotróficas em leite e derivados fluidos pasteurizados - Teixeira Coelho, Dilson; Blunck Bragança Coelho, Elizete (Revista Ceres, 2025)
To determine the suitability of standard methods agar for the enumeration of psychrotrophs, standard methods agar, heart infusion agar, tryptone glucose extract agar, trypticase soy agar and Rogosa agar were used as the plating media. The differences in psychrotrophic counts when the different media were used were significant at P = 0.10. The highest counts were observed when heart infusion agar was used as the plating medium. This was followed by trypticase soy agar, Rogosa agar, tryptone glucose extract agar and standard methods agar.